Apollo 13 - Grazer, Brian; Howard, Ron; Image Entertainment; Universal Pictures ([California] : Universal Studios, 1995)
It had been less than a year since the first man walked on the Moon, but to the American public, Apollo 13 was just another'routine' space flight. That is until the words pierced the immense void of space:'Houston, we have a problem.' Stranded in a crippled spacecraft 205,000 miles from Earth, astronauts Jim Lovell, Fred Haise, and Jack Swigert fight a desperate battle to survive. Meanwhile, at Mission Control, astronaut Ken Mattingly, flight director Gene Kranz, and the efforts of a heroic ground crew race against time -- and the odds -- to bring the men home
Based on the book Lost moon by Jim Lovell & Jeffrey Kluger
Title from title screen
Director of photography, Dean Cundey ; art directors, David J. Bomba, Bruce Alan Miller ; editors, Dan Hanley, Mike Hill ; music, James Horner ; costume designer, Rita Ryack ; production designer, Michael Corenblith ; visual effects supervisor, Robert Legato ; screenplay, William Broyles, Jr. & Al Reinert
Cast: Tom Hanks, Bill Paxton, Kevin Bacon, Gary Sinise, Ed Harris, Kathleen Quinlan, Mary Kate Schellhardt, Emily Ann Lloyd, Miko Hughes
DVD Format
Dolby Digital
Keywords: Apollo 13 (Spacecraft) -- Drama; Project Apollo (U.S.); Space vehicle accidents -- Drama; Space rescue operations -- Drama; Space flight to the moon -- Drama